2001
DOI: 10.5694/j.1326-5377.2001.tb143620.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of an interventional program for scabies in an Indigenous community

Abstract: Objective To implement an intervention program for reducing the prevalence of scabies in a large Northern Territory Aboriginal community. Design Prospective, longitudinal screening, intervention and follow‐up study. Participants and setting All children aged 5 years and under in one of the largest Aboriginal communities in the Northern Territory, total population, approximately 2200 (95% Indigenous). Main outcome measures A decrease in prevalence of scabies, infected scabies and non‐scabies pyoderma over seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 15 publications
0
62
0
Order By: Relevance
“…Whilst mass drug treatment with scabicides can produce short-term reduction in scabies disease burden [29], most experts believe that a sustained reduction requires an integrated approach that includes the following elements: public health education, improved case management, improved drug supply and potentially improvements in personal hygiene practices [18],[30]. Intervention studies in the Pacific region aimed solely at scabies control have been shown to achieve their aim of controlling scabies with a flow-on effect on scabies-associated impetigo, but they have had less effect on non-scabies impetigo [10],[31]. The finding of a large burden of impetigo independent of scabies in school-aged children in our study suggests that the case may be the same in Fiji [9],[11].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst mass drug treatment with scabicides can produce short-term reduction in scabies disease burden [29], most experts believe that a sustained reduction requires an integrated approach that includes the following elements: public health education, improved case management, improved drug supply and potentially improvements in personal hygiene practices [18],[30]. Intervention studies in the Pacific region aimed solely at scabies control have been shown to achieve their aim of controlling scabies with a flow-on effect on scabies-associated impetigo, but they have had less effect on non-scabies impetigo [10],[31]. The finding of a large burden of impetigo independent of scabies in school-aged children in our study suggests that the case may be the same in Fiji [9],[11].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial reductions in the prevalence of scabies in endemic settings have previously been described with mass community treatment using oral ivermectin [17] and topical permethrin [18],[19]. However, sustainability has been difficult to achieve [2],[12], particularly where there is high mobility between communities and households.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pathology directly attributable to scabies, it is a major initiating factor for streptococcal pyoderma, which in term is linked to renal and heart disease [1]. This association has led to concerted efforts to reduce prevalence of scabies and subsequent skin infections in settings where infestation is endemic, with studies demonstrating a link between scabies control and reduced incidence of post-streptococcal sequelae [2,3]. …”
Section: Introductionmentioning
confidence: 99%